97 Association between hypertensive disorders of pregnancy and later risk of cardiovascular outcomes. (May 2019) - Oliver-Williams, Clare; Stevens, David; Payne, Rupert; Wilkinson, Ian; Smith, Gordon; Wood, Angela
Abstract : Introduction: Hypertensive disorders of pregnancy, especially pre-eclampsia, are associated with greater cardiovascular disease risk. However, the risk of specific cardiovascular outcomes associated with pre-eclampsia or gestational hypertension is unclear. Methods: Cox regression analysis compared rates of 19 cardiovascular outcomes in women with and without a history of pre-eclampsia and gestational hypertension, using electronic health records from women with one or more live births in England, 1997–2015. Results: The cohort comprised 6, 333, 053 women, 276, 389 and 223, 715 pregnancies were complicated by gestational hypertension and pre-eclampsia, respectively. During 61.7 million person-years of follow-up, the incidence of any cardiovascular events for normotensive women, women with prior gestational hypertension and women with prior pre-eclampsia were: 39.95/100 000 person-years [95% CI, 39.05–40.87] (no. of CVD events=7, 474), 62.24/100 000 person-years [95% CI, 56.67–68.20] (no. of CVD events= 469), and 73.72/100 000 person-years [95% CI, 67.20–80.71] (no. of CVD events=469), respectively. Compared with women with normotensive pregnancies, there was a greater risk of any cardiovascular event for women with previous gestational hypertension, adjusted HR (aHR) = 1.45 (1.31, 1.61), and pre-eclampsia, aHR = 1.69 (1.53–1.87). A history of gestational hypertension was most strongly associated with cardiomyopathy, aHR = 2.10 (1.52–2.89), and ischemic stroke, aHR = 1.79 (1.36–2.35). Women with two or more pregnancies with gestational hypertension were at greatest risk of stroke, aHR = 2.61 (1.91, 3.57), specifically ischemic stroke, aHR = 3.47 (2.38, 5.06). Women with a history of pre-eclampsia were at greatest risk of acute myocardial infarction, aHR = 3.08 (2.27, 4.16), and cardiomyopathy, aHR = 2.43 (1.78–3.31). Two or more pregnancies with pre-eclampsia was most strongly associated with ischemic stroke, aHR = 3.80 (2.53, 5.73) and acute myocardial infarction, aHR = 3.18 (1.91, 5.28). Conclusions: This is the first study to compare the risk of a spectrum of CVD events for women with pre-eclampsia or gestational hypertension. Women with either previous gestational hypertension or pre-eclampsia are at increased risk of a range of cardiovascular outcomes compared to women with normotensive pregnancies. Associations were stronger with pre-eclampsia than gestational hypertension, and increased with a greater number of affected pregnancies. Gestational hypertension was most strongly associated with strokes, in particular ischemic stroke, and pre-eclampsia was most strongly associated with acute myocardial infarction and cardiomyopathy. Conflict of Interest: None